Smart applications and data analysis : third International Conference, SADASC 2020, Marrakesh, Morocco, June 25-26, 2020, Proceedings /: third International Conference, SADASC 2020, Marrakesh, Morocco, June 25-26, 2020, Proceedings. (2020) - Unknown
No abstract available